Remaking the Postwar World Economy - Burnham, P. author. aut Link
VIII, 236 p.
Keywords: Peter Burnham presents a detailed, archive-based account of the keys aspects of international monetary relations in the 1950s focusing in particular on Anglo-American policy surrounding the restoration of sterling convertibility. He argues that in 1952 the British government had a unique opportunity to take an almost revolutionary step in the external field to transform the international political economy (through the abolition of the fixed rate system, the International Monetary Fund, and the European Payments Union) and restructure Britain's domestic economy to tackle longstanding productivity, export and labour market problems.